Values in the contemporary Russian society - Andreev, Andrei (Przegląd Wschodnioeuropejski, 2018)
The report highlights the results of sociological studies devoted to the value system of the Russian society. Value priorities of Russians are considered in dynamics and in comparison with other European countries. In the light of empirical data various stereotypes and autostereotypes of national identity are critically analyzed, including the widespread myths about Russians’ special inclination towards collectivism and the lack of civil society in Russia. On the basis of data obtained by an original method of psychosemantic sounding the deep structures of the collective psyche together with the specific social representations of Russians and the “world view” that the majority of them share are analyzed. Considerable attention is also paid to the subject-matters of national pride, and to the peculiarities of Russian historical consciousness. On the basis empirical data collected by means of sociological research the question of Russia’s place in the system of relations of East – West is posed and discussed.